Effect of color differences on elastomeric ligatures adhesion on streptococcus mutans in saliva liquid - Baharuddin M. Ranggang; Ratna Dewi (DiscoverSys Inc., 2020)
Objective: Of this study was to determine the effect of color differences in elastomeric ligatures on the adhesion of streptococcus mutans in salivary fluidMaterial and Methods: Type of research used was laboratory experimental with cross sectional study, using elastomeric ligatures 10 pieces of orthodontic elastomeric ligatures dark clear fruits. The samples were then divided into 2 groups. Each group of samples was each immersed in 100 cc of artificial saliva pH 4 which had been given each cc of streptococcus mutans and cultured in the media to see the number of colonies attached to elastomeric ligatures. The results of calculating the number of colonies were then analyzed using the SPSS version 24 program and using the Independent t test with a significant value of 0.05.Results: The results showed that there are significant differences between the ligatures elastomeric orthodontic dark and elastomeric ligatures clear.Conclusion: Elastomeric ligatures darker color have more adhesion to streptococcus mutans when compared to adhesion streptococcus mutans to elastomeric ligatures clear.